ELABORACIÓN DE UN MANUAL DE PROCEDIMIENTOS CONTABLES PARA LA COOPERATIVA DE AHORRO Y Crédito VILCABAMBA CACVIL - Capa Aguilera, Cecilia Maribel (2020)
This thesis work called “ELABORATION OF A MANUAL OF ACCOUNTING PROCEDURES FOR THE SAVINGS AND CRÈDITO COOPERATIVA VILCABAMBA CACVIL”, was carried out as a support tool for the administrative, employees and workers of the Cooperative; through the application of methods and techniques that allowed to detect possible difficulties in the management of accounting activities through information gathering and the respective analysis, so that the staff knows the current situation of the accounting procedures performed by the entity. In order to achieve the above, it was necessary to comply with the objectives set out in the thesis work, for which the theoretical foundation of the policies, procedures and standards applicable to the development of the cooperative's accounting activities was carried out, which served as a basis for the development of work. Then it preceded to design accounting policies for each of the activities that are carried out in the accounting department of the cooperative based on the rules established in the Unique Account Catalog issued by the Superintendence of Popular and Solidarity Economy, the functions and Responsibilities within the accounting department. Then the respective procedures were defined according to each accounting policy in order to control the order of the different activities carried out by the accounting department, they help the managers of the cooperative to 5 fulfill their functions with veracity and accuracy when presenting the information Accounting and financial. Finally, the accounting procedures manual was designed which contains the results with their respective flowcharts; This document will allow the manager and managers to make correct decisions that contribute to the continuous development of the cooperative. As a conclusion, it was determined that the manual of accounting procedures for the Vilcabamba Savings and Credit Cooperative constitutes a tool that allows the directors of the entity to have an order to record the accounting activities, so it is recommended to take into account this manual which was elaborated to contribute to a better optimization of resources and time, contributing in this way to make the cooperative more efficient in each one of the operations carried out.